Effects of liquid crystalline ordering on the luminescence spectra of model compounds with packing-sensitive molecular structure - Zavora, L.N.; Serbina, M.I.; Kasian, N.A.; Gurkalenko, Yu.A.; Shershukov, V.M.; Lisetski, L.N. (Functional Materials, 2009)
Luminescence spectra in liquid crystalline (LC) solvents were measured for stilbene, p-terphenyl, o-POPOP, 2-(1-naphtyl)-5-phenyloxazole and other compounds commonly used as luminophores or scintillators. The choice of substances was prompted by the ability of their molecules to assume different predominant conformations in different phase states (e.g., standard organic solution vs. melt-grown single crystal). For each compound studied, the luminescence spectra were compared within the sequence "standard organic solution - solution in LC matrix - single crystal". Several distinct cases could be singled out, with the luminescence peak λmax shifted to longer wavelengths, to shorter wavelengths, remaining essentially unchanged, or being split into two separate peaks corresponding to two conformations with close distribution probabilities. For each compound, the observed luminescence behavior could be easily associated with the corresponding changes in the effective molecular shape supposedly induced by the LC and crystal ordering. The obtained data could serve as a basis for future search of efficient liquid crystalline scintillators.